FOTOGRAFI STILL LIFE MINIATUR MOBIL EROPA SEBAGAI MEDIA PROMOSI TUKSEDO STUDIO - I Made Ananda; I Ketut Sida Arsa; Amoga Lelo Octaviano (Retina Jurnal Fotografi, 2023)
The era of digitalization is one of the factors that opens the door to the global market. Digitalization makes it easier for local producers to advertise their products through social media, with Still Life Photography. The internship at Tuksedo Studio is carried out to improve knowledge, photography skills, and understand the conditions of the industrial world firsthand. With the problems studied regarding the use of Still Life in miniature European cars at Tuksedo Studio as a promotional medium, including the process and how it impacts. The internship program aims to know, understand, and master the Still Life used at Tuksedo Studio as a promotional medium on Instagram. This writing uses the method of observation, interviews, and documentation. During this MBKM internship, the author gained more knowledge at Tuksedo Studio than at university because college learning activities were more limited while internships gained experience using the Blackmagic Pocket Cinema Camera 4K camera, Tokina Lens 12-28mm f./4 AT-X Pro , Sigma 18-35mm F1.8 DC HSM Lens APS-C For Canon , Zhiyun CRANE 3 Lab Handheld Stabilizer. Using software to support the editing such as Adobe Lightroom, Adobe Photoshop, Davinci Resolve, Adobe Indesign, Adobe PremierePro. The knowledge gained while in college such as Still Life Techniques, Basic Photography Techniques, Use of Lenses and the effects of each lens, is useful in carrying out the internship. So between theory and practice gained in college, it is appropriate and useful in an internship at Tuksedo Studio.